Diseño y rehabilitación del camino vecinal Pelejo – Papaplaya - Pinedo Delgado, Andres (2010)
In recent years the country has gone through a difficult economic situation and order public which particularly affects rural areas, both in productive activity as in the situation of roads and roads that allow their articulation with the most dynamic areas in the jungle and thus further deteriorating their life conditions. In our country, the road system is still many shortcomings, so no is .llega to meet the needs of peoples, especially in places more away; this leads to the annual production of those areas affected, why products can not reach the main markets in the area. The construction of the road Pelejo - Papaplaya becomes the continuation of the Pongo previously executed road Caynarachi - Barranquita - Pelejo and is part of this major project it consists of the construction of the road level road said that seeks integration between terrestrial environment existing villages in areas · Lower, Huallaga Valley Caynarachi and Chipurana, This section seeks to reach the Papaplaya District. In our region we can see that there are still districts, towns that They do not have their roads and the best if there are these, most part are dirt roads that do not meet the Technical Specifications minimum for efficient service. Thus understood, the transcendental importance of road networks and the imperious need for an efficient road system that generates progress and social welfare, I have elaborated this thesis work, terming "Geometric Design Vecinal Pelejo- Papaplaya road. "The project basically involves the study of the main critical areas that have the area such as slope stabilization, shaping embankments, removal of organic material and a layer claimed to improve! to c.apa rolling.